Relationship between leg muscle strength and leg length and 100-meter running performance - Hartanto, Hartanto; Bildhonny, Achmad Furqon; Dardiri, Aang Ghunaifi (Universitas Tanjungpura, 2026)
Background. Physical Education, Sports, and Health has a role as a means of supporting physical growth, mental development, mastery of motor skills, increasing knowledge and reasoning power, internalizing values (such as ethics, mentality, sportsmanship, spirituality, and social), as well as the formation of a healthy lifestyle, all of which are directed at supporting physical and spiritual growth and development in a balanced and quality manner. Objectives. The study aims to ascertain the correlation between leg strength and leg length and the pace of a 100-meter race among senior high school students at MA Zainul Hasan Probolinggo. Methods. The methodology used in this study is correlation research. Additionally, this study is frequently referred to as non-experimental since the researcher does not have control over and is not able to change the variables in the study. Due to the vast size of the population in this study, the researcher employed Simple Random Sampling. The sample is a subset of the target population that the researcher intended to use to generalize the target (Sugiyono, 2017). The sample size for this study was 15 individuals. This research used a meter measuring instrument, a running test, and a vertical leap as the data collecting methods. Results. According to external research, the outcomes at MA Model Zainul Hasan Probolinggo are 0.38.1. The students at MA Model Zainul Hasan Probolinggo have a meaningful or significant association between their leg muscle strength and their 100-meter running time. In MA Model Zainul Hasan Probolinggo students, the F. Change value is 0.37. 2) The Sig. F change value of 0.45 indicates that there is a substantial link between leg length and 100-meter running performance. 3) There is a significant correlation between leg muscle strength, leg length, and 100-meter running achievement in MA Model Zainul Hasan Probolinggo students. The value between leg muscle strength, leg length, and the outcome of the 100-meter run is 0.38 in MA Model Zainul Hasan Probolinggo students. Conclusion. This study concluded that leg muscle strength and leg length have a significant influence on 100-meter running performance at MA Model Zainul Hasan Probolinggo students. Therefore, it is necessary to carry out supporting training so that all students can achieve 100-meter running performance